Practical risk management for EPC/design-build projects : manage risks effectively -- stop the losses - Salmon, Walter A. (Wiley Blackwell, 2020)
Many of the books on construction risk management concentrate on theoretical approaches to the accurate assessment of the overall risks of taking on a new project. Less attention is paid to the typical risks to which the operational level of a project is exposed and how operational managers should approach those risks during project implementation. This book identifies precisely where the major EPC/Design-Build risks occur within an operational framework and shows how best to deal with those risks. The book attempts to offer practical advice, approaches and tools for dealing with risks to which the various operational departments are exposed.